Characterization of the In Situ‐Formed Oxide Layer at the Steel Melt/Carbon‐Bonded Alumina Interface. Issue 2 (17th December 2019) - Zienert, Tilo; Dudczig, Steffen; Malczyk, Piotr; Brachhold, Nora; Aneziris, Christos G.
Abstract : The surface structure development of the in situ‐formed oxide layer on carbon‐bonded alumina refractory samples immersed in liquid 42CrMo4 steel at a temperature of 1650 °C is studied. The surface morphology is characterized using areal parameters such as the developed interfacial area ratio S dr, the texture aspect ration S tr, the arithmetic mean peak curvature S pc, the density of peaks S pd, and the maximum height S z defined in ISO 25178‐2:2012 and on the basis of own defined parameters using laser‐optical measured line profiles of the surface's height. The development of the surface morphology is found to be independent of the oxygen content of the steel melt at immersion time. The formed crystal structures are based on alumina and an (Al, Fe, Mg, Mn)‐containing spinel. The spinel's lattice parameters are found to vary between 8.0367 and 8.1194 Å corresponding to oxygen contents of the steel melt between 30 and 85 ppm. Abstract : The surface structure development of the in situ‐formed oxide layer on carbon‐bonded alumina refractory samples immersed in liquid 42CrMo4 steel at a temperature of 1650 °C is studied using laser‐optical microscopy. The formed crystal structures are based on alumina and an (Al, Fe, Mg, Mn)‐containing spinel.